The comparison of clinical and computerized measurement of sitting balance in stroke patients and healthy individuals - Ozdil, Aytul; Iyigun, Gozde; Kalyoncu, Cem (Ios Press, 2019)
BACKGROUND: Balance problems are common after stroke. OBJECTIVE: The aims of this study was to compare the results of computerized and clinical sitting balance measurements in stroke patients and healthy individuals and to identify the agreement and relationship between the two measurement methods in stroke patients. METHODS: This study included 30 chronic stroke patients and 30 age-matched healthy individuals. A force platform chair was used for the computerized and the Function in Sitting Test (FIST) was used for the clinical sitting balance measurement. RESULTS: The sitting balance of the stroke patients, measured with computerized and clinical measurements, were still affected in the chronic phase. The CoP deviation (eyes-open and eyes-closed) was higher whereas the FIST score was lower in the stroke group than the healthy group (p < 0.05). The computerized sitting balance measurements [eyes-open (r = -0.177, p = 0.349) and eyes-closed (r = -0.294, p = 0.114)] CoP deviation was not correlated with the FIST scores (p < 0.05). However, there was an excellent agreement (96.6%) between the methods. CONCLUSION: The results of this study implies that both the computerized and clinical sitting balance measurements can be used objectively for the assessment of sitting balance but the computerized methods might be preferable due to requiring shorter time with less intra-tester variability.
Keywords: Stroke; force platform; sitting balance; function in sitting